(untitled) (Al-Aasar, 2025)
The Ottoman Empire remained the center of the Islamic world and a symbol of the Islamic Caliphate for centuries. Established in 1299, this great empire, at its peak, spanned across three continents—Europe, Asia, and Africa—providing political, military, economic, and cultural leadership to the Muslim world. However, during the 19th and 20th centuries, internal and external factors led to the decline of the Ottoman Empire, ultimately resulting in the formal abolition of the Ottoman Caliphate in 1924. With this, the Muslim world entered a new era where various movements and ideological trends emerged in pursuit of Islamic unity and the restoration of Islamic identity in the absence of the Caliphate.After the abolition of the Caliphate, modernism, nationalism, and secularism were promoted in Turkey under the leadership of Mustafa Kemal Atatürk. Efforts were made to suppress Islamic identity, leading to the abolition of Islamic laws, the ban on the call to prayer (Adhan) in Arabic, and state control over Islamic institutions. However, to preserve Islamic identity and promote the idea of restoring the Caliphate, various Islamic movements emerged in Turkey and other Muslim countries, including the Muslim Brotherhood (Ikhwan-ul-Muslimoon), Jamaat-e-Islami, and other reformist and political Islamic movements.The fall of the Ottoman Empire is considered one of the most significant political and civilizational transformations of the 20th century, paving the way for the end of the Caliphate and the establishment of modern nation-states. After the formal end of the Caliphate in 1924, Turkey adopted the path of secularism and Western reforms, which sought to marginalize Islamic traditions and values at the state level. Under Atatürk’s leadership, radical reforms reshaped Turkey’s religious and political landscape, including restrictions on Islamic institutions, changes in the Arabic script, and state control over mosques and madrasas. These transformations triggered strong reactions not only within Turkey but across the Muslim world.Several Islamic movements, which had previously supported the Ottoman Caliphate, reorganized themselves in response to the new situation. The Muslim Brotherhood, Jamaat-e-Islami, and other global Islamic movements not only intellectually analyzed Turkey’s situation but also reflected its influence in their ideological frameworks. On the other hand, within Turkey, Islamic-oriented movements such as Necmettin Erbakan’s Milli Selamet Partisi (National Salvation Party) and later the Refah Party (Welfare Party) became active in restoring Islamic identity.This analysis provides a comprehensive study of Islamic movements in Turkey after the fall of the Ottoman Caliphate, focusing on their background, ideologies, objectives, challenges, and impact. Through this research, we will explore how these movements influenced Turkish politics, society, and Islamic identity and to what extent they aligned with global Islamic movements.